Transcriptional Organization of the Ribosomal RNA Cistrons in Escherichia Coli - Doolittle, W. Ford (1971)
The data presented support the hypothesis that 16S, 23S, and 5S ribosomal RNAs of Escherichia coli are transcribed in vivo from transcriptional units consisting of single cistrons for these species arranged in the order 16S-23S-5S, with transcription beginning at the 16S end.